Implementation of a Quality Management System According to ISO 9001:2015: The Case of a Textile Company - Buele, Jorge (2024)
This textile company is dedicated to the industrial washing, drying, and dyeing of garments, according to the indications of its customers. The global economic recession and many competitors have caused the top management to decide to implement a quality management system, which allows it to better manage its resources and thus provide a better service. Therefore, the implementation of a system based on the requirements established by the UNE-EN ISO 9001:2015 standard is proposed. The starting point is the initial analysis of the organization’s context, identification of stakeholders, risks, and opportunities, which allows redefining internal processes. The development of a complete documentary structure allows a better organization of the activities performed by the processes and their interactions. To validate the system, an internal audit is carried out, verifying the degree of compliance with the requirements. With the active participation of all the personnel and with the top management as a leader, there is an improvement in the efficiency of the company, establishing a reference for other organizations in the sector.